IN SITU HIGH-PRESSURE AND HIGH-TEMPERATURE BUBBLE GROWTH IN SILICIC MELTS - Martel C.; Bureau H. (My University, 2001)
We present the first investigation of in situ high-pressure and high-temperature bubble growth in silicic melts. In a hydrothermal diamond-anvil cell, a haplogranite melt (79 wt% SiO2) is hydrated then subjected to cooling and decompression. With decreasing pressure, water exsolves from the melt and bubbles grow. The whole experiment is observed through an optical microscope and video-recorded, so that bubble nucleation, bubble growth, and the glass transition are directly monitored. Bubbles nucleate and expand in melt globules having radii from 15 to 70 μm. Bubbles reached 3.6-9.1 μm in radius within 6.1-11.7 s (until the glass transition is attained) while temperature decreases from 709-879°C to 482-524°C, corresponding to decompressions from 7.0-21.9 to 3.4-15.2 kbar. Bubbles nucleated either in a single event occurring within the first second or in successive pulses over a period of up to 7 s when the melt globules are in contact with a diamond culet of the cell. In these experiments, bubble growth can be fitted to the cube root or a logarithm of time, mainly ascribable to the combination of large water oversaturations due to rapid cooling and decompression. At pressures of 3.4-15.2 kbar, we measure glass transition temperatures that are 20-80°C higher than those calculated at atmospheric pressure.
Keywords: BUBBLES; HIGH PRESSURE; HIGH TEMPERATURE; GROWTH RATES; SILICATE MELTS